Avaliação da assistência pré-natal e puerperal desenvolvidas em região do interior do Estado de São Paulo em 2005 - Parada, Cristina Maria Garcia de Lima [UNESP] (FapUNIFESP (SciELO), 2008)
Objectives: to evaluate the structure and process of the prenatal and puerperal care given by Direção Regional de Saúde (DIR) XI, at the city of Botucatu, State of São Paulo, Brazil. Methods: an evaluation of resources and activities developed during prenatal and puerperal care in twenty municipalities comprising DIR XI which had adhered the Prenatal and Birth Humanization Program until 2003. Interviews with city managers and analysis of 385 sampled patient charts taking into account recommendations by the Health Department. Results: structure analysis showed that caregiving was centered on medical work; basic equipment and instruments were available; 85.2% of patients began prenatal care with up to 120 days of pregnancy, and 75.9% had at least six prenatal consultations. The active search for absentees and strategies for early prenatal care initiation were observed in 30% and 50% of the municipalities, respectively. Process indicators showed that 3.6% of women had six prenatal consultations, one puerperal consultation, all basic exams and tetanus immunization. Recording of gestational age, arterial blood pressure and weight was of approximately 90%; 58.7% of the women underwent childbirth review and 31.5% were vaccinated. Conclusions: the performance of the set of activities is a challenge to prenatal care at DIR XI.
An evaluation of the prenatal and puerperal care provided in an upstate region of the State of São Paulo in 2005
Keywords: Evaluation; Humanization; Maternal-child health; Prenatal care; Program